COMMUNITY PERCEPTIONS OF HYDRO-CLIMATE RISKS ON THE SOCIO-ECONOMIC ACTIVITIES OF THE POPULATIONS OF THE LOW VALLEY OF OUEME (BVO) IN WEST AFRICA - AIMADE, Hilaire; HEDIBLE, SIDONIE CLARISSE; ATCHADE, Gervais; VISSIN, EXPÉDIT WILFRID (My University, 2020)
The present research is to study local perceptions of the impacts of hydro-climatic risks on the socio-economic activities of the populations of the lower Ouémé Valley (BVO) in West Africa. To achieve this, the methodological approach applied, namely: documentary research, field surveys, data processing and analysis of results. In addition to data from surveys on the endogenous perceptions of populations on hydro-climatic risks, socio-anthropological surveys are carried out in the BVO and relate to a sample drawn by sampling at the household level. These results show that rain floods cause damage to agriculture for 61% of respondents, while drought only affects 39% of those surveyed. 59% of those questioned about the floods affect trade while for 41% the drought causes nuisances to this sector of activity. Regarding land transport, 59% of those questioned perceive that river floods are a nuisance while 41% of people think the opposite. Agriculture and river transport are the sectors most exposed to rain flooding for 73% and 77% of the respondents respectively.
Keywords: Lower Ouémé Valley; perception; hydro-climatic risk